From shame to sin : the Christian transformation of sexual morality in late antiquity - Harper, Kyle, 1979- (Revealing Antiquity, 2013)
The transformation of the Roman world from polytheistic to Christian is one of the most sweeping ideological changes of premodern history. At the center was sex. Kyle Harper examines how Christianity changed the ethics of sexual behavior from shame to sin, and shows how the roots of modern sexuality are grounded in an ancient religious revolution.